THE TIMELINESS OF A REVISIONOFTHE TAX STATUS OF COOPERATIVESBASED ON A COMPARATIVE LAW ANALYSISIN THE LIGHT OF SUSTAINABLE DEVELOPMENTGOALS - Grau Ruiz, María Amparo (International Journal of Cooperative Law, 2025)
A brief review of the current regulations governingthe life of cooperatives in various countries around the world clearly highlights their weight in different societies, more or less advanced, andalso the influence of the current regulations ontheirdegree of development in any of these contexts.